تصميم آلات التشغيل المبرمجة ذات القيادة الرقمية CNC للتصميم والبناء الهيكلي - مقدسي, نبيل (Latakia University Journal -Engineering Sciences Series, 2019)
This paper studiessome issues in Computer Numerical Control operation and programming. It also tackles the issue of errors in machine tools, geometric errors, and thermal errors. The paper also studies some dynamic phenomenon and position errors that affect the accuracy and stability of the programmed operation tools and the effects of fixing operations on these machines, besides using control devices and electric servo devices. يتناول البحث دراسة بعض المسائل في تصميم آلات التشغيل ذات القيادة الرقمية المبرمجة CNC والتعرض إلى دراسة أخطاء آلات التشغيل The errors in machine tools والأخطاء الهندسية geometric errors والاخطاء الحرارية thermally errors 0 ويدرس بعض الظواهر الديناميكية وأخطاء التوضع التي تؤثر درجة دقة ومتانة آلات التشغيل المبرمجة وتاْثير عمليات التثبيت على هذه آلالات واستخدام أجهزة القيادة والتحكم وجمل نقل الحركة المساعدة للمحركات الكهربائية servo drive 0